Response of IAR frequency scale to solar and geomagnetic activity in solar cycle 24 - Alexander S. Potapov; Tatyana N. Polyushkina (AIMS Geosciences, 2020)
The ionospheric Alfvén resonator (IAR) is an integral element of the entire ionosphere-magnetosphere system. It plays an essential role in energy exchange and interaction between the magnetosphere and ionosphere. The parameters of this resonator reflect the state of the ionosphere. The purpose of this study was to study three types of IAR frequency modulation (daily, seasonal and solar-cyclic) and to identify their relationship with solar and magnetic activity. We used the results of magnetic observations of the IAR emission at the Mondy mid-latitude observatory for the 24th solar activity cycle from 2009 to 2019. The dependence of the difference in the neighboring harmonics frequencies (i.e., the emission frequency scale) on solar activity (the sunspot number) and on the magnetic indices Kp, Dst and AE was studied. The correlation between the frequency scale and the indices of solar and magnetic activity was investigated at different time scales by comparing the variations in daily, monthly, and annual averages. The dependence of the IAR frequency scale on solar activity turns out to be much closer than the same dependence of any of the three magnetic indices. The closest relationship is exhibited between the annual average values of the frequency scale, on the one hand, and the sunspot number and the Dst index, on the other. This result is interpreted as a demonstration of the cumulative effect of solar activity on the state of the ionosphere and, first of all, on the electron concentration in the F2 region of the ionosphere.